2023
DOI: 10.17159/sadj.v78i04.15177
|View full text |Cite
|
Sign up to set email alerts
|

A pre and post-test assessment of oral health intervention: caregivers’ knowledge and attitudes at long-term care facilities in the eThekwini district, KwaZulu-Natal.

Abstract: Oral health remains a neglected aspect of health care among vulnerable populations residing at long-term care facilities. Routine oral health education and training for caregivers have the potential to improve oral health provision. Aims and Objectives To determine the effect of an oral health intervention on caregivers’ knowledge and attitudes. Methods This exploratory study utilised a pre/post-test assessment approach. A total of participated. A pre-test questionnaire was distributed among 145 caregivers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…38 This finding concurs with a similar study which reported improved knowledge among caregivers, following an oral health intervention. 39 Less than half of the caregivers (n=68; 46.9%) in the preintervention phase, agreed that loose teeth can sometimes be a sign of gum and bone disease, compared to 89% of caregivers (n=129) in the post-intervention phase who agreed with the statement. 38 Additionally, very few caregivers (n=17; 11.7%) in the pre-intervention phase reported that regular flossing was an important part of the oral hygiene regime, and that initial bleeding of the gums was normal, compared with 81 caregivers (55.9%) in the post-intervention phase who agreed.…”
Section: Stage 3: Review Of the Interventionmentioning
confidence: 97%
“…38 This finding concurs with a similar study which reported improved knowledge among caregivers, following an oral health intervention. 39 Less than half of the caregivers (n=68; 46.9%) in the preintervention phase, agreed that loose teeth can sometimes be a sign of gum and bone disease, compared to 89% of caregivers (n=129) in the post-intervention phase who agreed with the statement. 38 Additionally, very few caregivers (n=17; 11.7%) in the pre-intervention phase reported that regular flossing was an important part of the oral hygiene regime, and that initial bleeding of the gums was normal, compared with 81 caregivers (55.9%) in the post-intervention phase who agreed.…”
Section: Stage 3: Review Of the Interventionmentioning
confidence: 97%